The impact of implementing a hospital electronic prescribing and administration system on clinical pharmacists' activities - a mixed methods study - Monsey McLeod; Georgios Dimitrios Karampatakis; Lore Heyligen; Ann McGinley; Bryony Dean Franklin (BMC, 2019)
Abstract Background The increasing adoption of hospital electronic prescribing and medication administration (ePA) systems has driven a wealth of research around the impact on patient safety. Yet relatively little research has sought to understand the effects on staff, particularly pharmacists. We aimed to investigate the effects of ePA on pharmacists' activities, including interactions with patients and health professionals, and their perceptions of medication safety risks. Methods A mixed methods study comprising quantitative direct observations of ward pharmacists before and after implementation of ePA in an English hospital, and semi-structured interviews post-ePA. Quantitative data comprised multi-dimensional work activity sampling to establish the proportion of time ward pharmacists spent on different tasks, with whom and where. These data were extrapolated to estimate task duration. Qualitative interviews with pharmacists explored perceived impact on (i) ward activities, (ii) interactions with patients and different health professionals, (iii) locations where tasks were carried out, and (iv) medication errors. Results Observations totalled 116 h and 50 min. Task duration analysis suggested screening inpatient medication increased by 16 mins per 10 patients reviewed (p = 0.002), and searching for paper drug charts or computer decreased by 2 mins per 10 patients reviewed (p = 0.001). Pharmacists mainly worked alone (58% of time pre- and 65% post-ePA, p = 0.17), with patient interactions reducing from 5 to 2% of time (p = 0.03). Seven main themes were identified from the interviews, underpinned by a core explanatory concept around the enhanced and shifting role of the ward pharmacist post-ePA. Pharmacists perceived there to be a number of valuable safety features with ePA. However, paradoxically, some of these may have also inadvertently contributed to medication errors. Conclusion This study provides quantitative and qualitative insights into the effects of implementing ePA on ward pharmacists' activities. Some tasks took longer while others reduced, and pharmacists may spend less time with patients with ePA. Pharmacists valued a number of safety features associated with ePA but also perceived an overall increase in medication risk. Pharmacy staff demonstrated a degree of resilience to ensure 'business as usual' by enhancing and adapting their role.